Deconstructing Gender and Class Discourse in Satirical Cinematic Language through de Beauvoirian Lens - Rahman, Fadhlur; Yuzar, Ella; Kholid, Mohammad; Nurlaila, Nurlaila (Saree: Research in Gender Studies, 2025)
This paper aims to explore the utilization of Simone de Beauvoir’s feminist-philosophical theory in a contemporary media context, specifically in Ruben Östlund's film Triangle of Sadness, to gain a comprehensive understanding of the mechanism of gender and class identity construction. The critical discourse analysis was then employed to analyse the data, allowing for the identification of language and symbolic patterns that reflect patriarchal and capitalist social norms. De Beauvoir’s theories of gender and class act as the theoretical foundation for this paper, comprehend the constitution of identity as socially constructed, and provide a critical analytical tool for unravelling how established norms organize hierarchies and divisions of power within society. The results show that Triangle of Sadness is a satirical narrative that effectively deconstructs gender and class social structures. Through de Beauvoirian’s analytical lens, the film demonstrates how extreme situation that challenge dominant norms could shake social constructions of identity. Scenes ranging from an argument over who pays for dinner to power dynamics on a cruise ship, vividly demonstrate how gender and class shape identity and social interactions. This study affirms that de Beauvoirian’s theoretical framework remains relevant and pertinent for re-interpreting contemporary media discourse, particularly in comprehending the tension and conflict between social structures.   Abstrak Tujuan penelitian ini adalah untuk mendapatkan pemahaman yang lebih dalam tentang mekanisme pembentukan identitas gender dan kelas melalui teori feminisme-filosofis Simone de Beauvoir dalam konteks media kontemporer, khususnya melalui film Triangle of Sadness yang disutradarai oleh Ruben Östlund. Data dikumpulkan melalui analisis teks naskah film, artikel dan ulasan kritis. Studi ini kemudian menggunakan analisis wacana kritis untuk menganalisis penggunaan bahasa dan pola simbolik yang mencerminkan standar sosial, kapitalis dan patriarki. Pemikiran de Beauvoir menjadi landasan teoretis untuk memahami konstruksi identitas dan sosial, dan menjadi alat analisis kritis untuk mengungkap bagaimana norma-norma yang mapan mengatur hierarki dan pembagian kekuasaan di komunitas atau masyarakat. Hasil penelitian ini menunjukkan bahwa film Triangle of Sadness memupuk narasi satir secara efektif dan mendekonstruksi struktur sosial dan kelas. Film ini menunjukkan juga bagaimana situasi ekstrem yang menantang norma-norma dominan dapat mengubah pemahaman sosial tentang identitas kelas dan jender. Adegan-adegan yang ditunjukkan dalam film, seperti perdebatan panjang antara pasangan (tentang siapa yang harus membayar makan malam), hingga pergolakan dominasi struktur sosial dan dinamika kekuasaan di dalam kapal pesiar memberikan interpretasi baru dalam konstruksi sosial yang sebenarnya. Sehingga, kerangka teori feminisme-filosofis de Beauvoir masih sangat relevan dan tepat untuk menafsirkan kembali wacana, terutama dalam konteks pemahaman konflik dan ketegangan antara struktur sosial.